Characterization of an Enterococcus faecalis Bacteriophage vB_EfaM_LG1 and Its Synergistic Effect With Antibiotic - Song, Min; Wu, Dongmei; Hu, Yang; Luo, Haiyan; Li, Gongbo (Frontiers in Cellular and Infection Microbiology, 2021)
Enterococcus faecalis is a Gram-positive opportunistic pathogen that could cause pneumonia and bacteremia in stroke patients. The development of antibiotic resistance in hospital-associated E. faecalis is a formidable public health threat. Bacteriophage therapy is a renewed solution to treat antibiotic-resistant bacterial infections. However, bacteria can acquire phage resistance quite quickly, which is a significant barrier to phage therapy. Here, we characterized a lytic E. faecalis bacteriophage Vb_EfaM_LG1 with lytic activity. Its genome did not contain antibiotic resistance or virulence genes. Vb_EfaM_LG1 effectively inhibits E. faecalis growth for a short period, and phage resistance developed within hours. However, the combination of antibiotics and phage has a tremendous synergistic effect against E. faecalis, prevents the development of phage resistance, and disrupts the biofilm efficiently. Our results show that the phage-antibiotic combination has better killing efficiency against E. faecalis.